RESPONS PEMBERIAN JUS SAWI (Brassica rapa) TERHADAP HEMATOLOGI DAN KADAR ASAM URAT DARAH PADA TIKUS PUTIH (Ratus norwegicus) - Triastinurmiatiningsih, .; Moerfiah, .; Faisal, Muhammad (Universitas Pakuan, 2024)
This research is motivated by the fact that the mineral calcium is needed by the body for functional operations and bone health. Calcium needs for body operations include the formation of red blood cells. If blood cell formation is disrupted, it will cause anemia, which can lead to a calcium deficit that can lead to bone loss or what is known as osteoporosis. One of the plants that contain high calcium is mustard greens. The contents of mustard greens include protein, fat, carbohydrates, calcium, phosphorus, iron (Fe), vitamin A, vitamin B and vitamin C. However, green leafy plants such as mustard greens are thought to cause an increase in uric acid in the blood. In this research, mustard juice will be given as calcium intake to fulfill body operations, namely hematocrit levels and hemoglobin levels and blood uric acid levels. 18 white rats are grouped as follows: Group 1 with 4 mL/200g BW, group II 8 mL/ 200g and group III negative control treatment, each treatment was repeated 6 times, for 15 days. This research was designed using a 3x4 Factorial Completely Randomized Design, analyzed using ANOVA and Duncan's Test. The results obtained were that 8 mL/200G BW mustard juice could increase hemoglobin levels and did not increase uric acid levels.